Effect of mixing and ageing on the mechanical and self-healing properties of asphalt mixtures containing polymeric capsules - Norambuena-Contreras, J.; Yalcin, E.; Garcia, A.; Al-Mansoori, T.; Yilmaz, M.; Hudson-Griffiths, R. (Elsevier Sci Ltd, 2018)
In this paper, polymeric capsules with sunflower oil as the encapsulated rejuvenator were manufactured and added to asphalt mixtures to improve their self-healing properties. A capsule content of 0.5% by total mass of mixture was added to the asphalt samples. Physical, thermal and mechanical properties of the capsules were evaluated. Additionally, the effect of the mixing order and the ageing time on the mechanical stability and self-healing properties of asphalt mixtures with, and without, capsules were evaluated through stiffness modulus and flexural strength tests. Self-healing properties of asphalt mixtures were evaluated through three-point bending tests on cracked asphalt beams with, and without, capsules. In addition, capsules' distribution and their integrity inside the asphalt mixtures were analysed using X-ray computed tomography. The main results proved that the capsules can resist the mixing and compaction conditions and break inside the mixture releasing the encapsulated oil in small volumes. In addition, it was observed that the addition of capsules did not improve the stiffness modulus of asphalt mixtures compared to mixtures without capsules, and that the mixing order and the ageing time did not have a significant influence on the flexural strength of the mixtures. Moreover, the healing levels obtained by the mixtures varied depending on the order of addition of capsules, and mixtures with capsules showed higher healing levels than mixtures without capsules. Finally, the levels of healing for the mixtures without ageing were greater than those of mixtures after the ageing process. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Self-healing asphalt; Encapsulated rejuvenators; Mixing method; Ageing effect; Capsules distribution; Healing level